2005
DOI: 10.1111/j.1528-1167.2005.70004.x
|View full text |Cite
|
Sign up to set email alerts
|

First Epileptic Seizure Induced by Occupational Nickel Poisoning

Abstract: Summary: Toxic causes of seizures are numerous: alcohol and other substances of abuse, drugs, and industrial and household products. However, in the absence of a clearly suggestive history and/or associated symptoms and signs, identification of the toxic origin of new-onset seizures may be extremely difficult. We report here the case of a patient admitted in our hospital after a single generalized tonic-clonic seizure. The remarkable coincidence that a colleague of his, with whom he was working to clean the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Some studies have found increased risks of cerebrovascular disease, brain tumors, and neurodegenerative disease among people who have occupational exposure to chemicals [4][5][6][7], but few studies have reported on the association between specific occupations and incidence of epilepsy [8,9]. One such study reported a relationship between first epileptic seizure and occupational nickel poisoning [9]. Most studies to date have been case-control studies, and most of these have used prevalent cases and relied on self-reporting for exposure assessment, which may lead to self-report and recall bias.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found increased risks of cerebrovascular disease, brain tumors, and neurodegenerative disease among people who have occupational exposure to chemicals [4][5][6][7], but few studies have reported on the association between specific occupations and incidence of epilepsy [8,9]. One such study reported a relationship between first epileptic seizure and occupational nickel poisoning [9]. Most studies to date have been case-control studies, and most of these have used prevalent cases and relied on self-reporting for exposure assessment, which may lead to self-report and recall bias.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that the automatisms were related to NCSE, although behavioral changes due to VHE were considered in the differential diagnosis, because there were EEG findings with concomitant altered states of consciousness and then oral‐alimentary automatisms that they were due to focal status epilepticus. Focal seizures, especially from the temporal lobes, have been reported exceptionally with poisonings with methanol, nickel, carbon monoxide, lithium, or domoic acid (12, 13). They suggest a higher susceptibility of the temporal cortex to potentially epileptic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac manifestations of nickel carbonyl exposure may include myocarditis and electrocardiographic abnormalities, including QT prolongation and heart block [118]. Deaths are frequently due to acute lung injury or cerebral edema [103,114,115]. In survivors, a prolonged neurasthenic syndrome has been reported, lasting several months in some cases [118].…”
Section: Clinical Presentation and Lifethreatening Complicationsmentioning
confidence: 99%
“…Few nickel exposures result in a critical care admission. The exception is nickel carbonyl, which may cause multisystem toxicity, particularly involving the pulmonary system, within hours after significant inhalational exposure [115][116][117]. The severity of toxicity of nickel carbonyl has been compared with hydrogen cyanide [117].…”
Section: Clinical Presentation and Lifethreatening Complicationsmentioning
confidence: 99%